Representação da História e Registro de Identidade em Quarup, de Antonio Callado, e A Geração da Utopia, de Pepetela: nos impasses da modernidade - Farias, Vera Elizabeth Prola (2007)
Quarup, by Antonio Callado (1967), and A Geração da Utopia, by Pepetela (1992), have a strong political nature, referring, the first, directly to the Brazil's history from the 60 s, and the second, to the history of Angola on and after the struggle for anticolonial liberation as symbolic novels. Above all, they are narratives that operate in the paradigm of the modernity impasses, wich problematize the allocations identities as continuous / discontinuous movements from relations that the subject, communities, nations and institutions set eyes with the real imaginarily. The identity, topic that is common in both texts, allow us to find in their complexity, damaged societies and geopolitically marked that, in a dialectical movement announce and preannounce deep modifications, that are articulated in the narratives, in the instance of the history interweaving with the fiction. Both Quarup and A Geração da Utopia are narratives of a time, that capture symptoms, singularly privileged, from a deeper irrepressible history impulse - the absent causes - whose strength of inversion showns more intense in the first one, and can be recovered in the cracks of memory, by the second. Thus, the narratives are constructed on the logic and modernity basis - in an essentially utopic way - trying to capture their emergency by deed, expel residual traces of valuable indications of impossibilities. They gleam a radical dialogue between the history and the literature that no longer contents with a mere representation like the truth. It's not about texts that follow the history tangent by the use of true informations that are objects from history, but in a speech organized from a through fiction history. The incorporation of history on the narrative organization implies a critical look of the extratextual events that no longer satisfies the balance between the narrate and the describe, as trademarks of the historical romance. The story and the fable meet and exchange in figuration that reconciliate the real and the imaginary configuring the impossibility of reconstruction of a real/past without transpass the discourse process. The significances located in the fiction discourse empowers strategically the meanings of the culture in Brazil and in Angola, in the characters level that (un) focus on the complex relationship from the individual with the collective, wich is built from content as a "nation", "Utopia" and "colonialism."